Mortal gods : science, politics, and the humanist ambitions of Thomas Hobbes - Miller, Ted H., 1965- (Pennsylvania State University Press, 2011)
"Argues against the accepted idea that Thomas Hobbes turned away from humanism to pursue the scientific study of politics. Reconceptualizes Hobbes's thought within early modern humanist pedagogy and the court culture of the Stuart regimes"--Provided by publisher